2019
DOI: 10.4209/aaqr.2018.12.0476
|View full text |Cite
|
Sign up to set email alerts
|

EC/OC and PAHs Emissions from a Modern Diesel Engine with DPF Regeneration Fueled by 10% RME Biodiesel

Abstract: In this study, the effect of using a blended biodiesel fuel containing 10% rapeseed methyl ester (RME) on the composition and quantity of the chemicals emitted by a modern diesel engine was investigated. The diesel engine that was utilized fulfilled Japan's Post New Long Term emission standards and was equipped with an after-treatment system comprising a diesel oxidation catalyst and a catalyzed diesel particulate filter (c-DPF). Using the Japanese JE05 transient cycle as the testing cycle, the exhaust gas was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…Generally, this study observed low EFs of OC and EC from the exhaust particulate samples, suggesting that the DPF has a high effectiveness to remove particulate exhaust emissions. Shibata et al (2019) measured the carbonaceous aerosols emission from an engine with DPF and oxidation catalyst, and reported a reduction of 99.7% EC and 91.8% OC for diesel fuel, and 99.5% EC and 87.8% OC for B10 rapeseed methyl ester biodiesel blend, respectively. In this study, it was found that the EC contents emitted from both B0 and B5 fuels were very close to the detection limit over all three driving cycles.…”
Section: Oc and Ecmentioning
confidence: 99%
“…Generally, this study observed low EFs of OC and EC from the exhaust particulate samples, suggesting that the DPF has a high effectiveness to remove particulate exhaust emissions. Shibata et al (2019) measured the carbonaceous aerosols emission from an engine with DPF and oxidation catalyst, and reported a reduction of 99.7% EC and 91.8% OC for diesel fuel, and 99.5% EC and 87.8% OC for B10 rapeseed methyl ester biodiesel blend, respectively. In this study, it was found that the EC contents emitted from both B0 and B5 fuels were very close to the detection limit over all three driving cycles.…”
Section: Oc and Ecmentioning
confidence: 99%
“…It is highly likely that these particles are heavy hydrocarbons from incomplete combustion during the late fuel injection to regenerate the filter. High concentrations of polycyclic aromatic hydrocarbons (PAHs) have also been detected during active regenerations [49]. Regeneration studies have identified fueloriginated hydrocarbons [45], but low-volatility oil hydrocarbons have been also measured in significant amounts [10].…”
Section: Vehicle #1 Regenerationsmentioning
confidence: 99%
“…filter. High concentrations of polycyclic aromatic hydrocarbons (PAHs) have also been detected during active regenerations [49]. Regeneration studies have identified fueloriginated hydrocarbons [45], but low-volatility oil hydrocarbons have been also measured in significant amounts [10].…”
Section: Vehicle #1 Regenerationsmentioning
confidence: 99%
“…Diesel and D90B10 PMs exhibited higher EC2 than other EC. 267 Under DPF regeneration conditions, OC increased due to an additional fuel supply. BC and OM reduced with increasing λ in diesel engines.…”
Section: Chemical Characterization Of the Pmmentioning
confidence: 99%